Representations, imaginaries and mythologies: Meanings of the Greatest March in Chili - Basulto-Gallegos, Óscar; Riffo-Pavón, Ignacio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of the article is to theoretically operationalize the significant complementarity, of three levels of social meaning (social representations, imaginaries and mythologies), through the discursive construction in the Chilean digital alternative press. At the methodological level, qualitative content analysis is applied, analyzing two press releases belonging to El Desconcierto and El Mostrador, alluding to the theme of the Largest March in Chile that occurred during the Social Outburst of 2019. In terms of findings and Conclusions It is evident at a theoretical and operational level the close dialectic and complementarity between the three theoretical notions of significance mentioned.